Cognitive Reasoning for Compliant Robot Manipulation - Leidner, Daniel Sebastian; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
In order to achieve human-like performance, this book covers the four steps of reasoning a robot must provide in the concept of intelligent physical compliance: to represent, plan, execute, and interpret compliant manipulation tasks. A classification of manipulation tasks is conducted to identify the central research questions of the addressed topic. It is investigated how symbolic task descriptions can be translated into meaningful robot commands.Among others, the developed concept is applied in an actual space robotics mission, in which an astronaut aboard the International Space Station (ISS) commands the humanoid robot Rollin' Justin to maintain a Martian solar panel farm in a mock-up environment.
Introduction -- Fundamentals -- Classifying Compliant Manipulation -- Representations for Compliant Manipulation -- Planning Everyday Manipulation Tasks -- Compliance Parameterization and Task Execution -- Semantic Interpretation of Haptic Feedback -- Applied Intelligent Physical Compliance -- Conclusions.
Keywords: Control engineering; Robotics; Automation; Artificial intelligence; User interfaces (Computer systems).; Human-computer interaction; Control, Robotics, Automation; Artificial Intelligence; User Interfaces and Human Computer Interaction